1999
DOI: 10.1086/306852
|View full text |Cite
|
Sign up to set email alerts
|

The Radio‐Optical Jet in NGC 3862 from Parsec to Subkiloparsec Scales

Abstract: We have observed the radio source in NGC 3862 (3C264) simultaneously with the EVN and the MERLIN arrays, obtaining detailed images of its radio structure from parsec to sub-kiloparsec scales. 3C264 shows a one-sided jet, with evident variations in its morphological properties with distance. We have analyzed HST optical data of NGC 3862, finding a one-to-one correspondence between radio and optical features in the jet. The radio to optical spectral index is approximately constant along the jet. Synchrotron appe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 34 publications
4
26
0
Order By: Relevance
“…Both the jet and counterjet are embedded in a vast and diffuse region of low surface brightness emission, which seems to have been dragged toward the north, possibly revealing the existence of a high density intracluster medium. Simultaneous EVN and MERLIN observations at 5.0 GHz by Lara et al (1999); Baum et al (1997) showed for the first time the detailed structure of 3C 264 on sub-kiloparsec scales. It consists of a one-sided jet with evident variations in its morphological properties with distance: i) the strong core and innermost jet (0−10 pc); ii) a wellcollimated and narrow region (10−100 pc); iii) a region with strong widening, kinks, and filaments (100−300 pc); and iv) a faint and narrow region after a jet deflection (300−400 pc from the core).…”
Section: Notes On Individual Sourcesmentioning
confidence: 95%
See 2 more Smart Citations
“…Both the jet and counterjet are embedded in a vast and diffuse region of low surface brightness emission, which seems to have been dragged toward the north, possibly revealing the existence of a high density intracluster medium. Simultaneous EVN and MERLIN observations at 5.0 GHz by Lara et al (1999); Baum et al (1997) showed for the first time the detailed structure of 3C 264 on sub-kiloparsec scales. It consists of a one-sided jet with evident variations in its morphological properties with distance: i) the strong core and innermost jet (0−10 pc); ii) a wellcollimated and narrow region (10−100 pc); iii) a region with strong widening, kinks, and filaments (100−300 pc); and iv) a faint and narrow region after a jet deflection (300−400 pc from the core).…”
Section: Notes On Individual Sourcesmentioning
confidence: 95%
“…In Col. 8 we give the angular resolution of maps used to estimate the core coordinates. We use (v) for the detected objects whose coordinates are taken by the VLBA maps and (!n) for well known radiosources with public VLBI data: (!1) from Taylor et al (2006a), (!2) from Lara et al (1997); Baum et al (1997); Lara et al (1999), (!3) from Gentile et al (2007) and (!4) from Venturi et al (1995). We use (xn) for undetected radiosources for which coordinates are taken from: (x1) , from NVSS ; (x2) from NED; (x3) from FIRST; (x4) from radio data of ; (x5) from Ledlow & Owen (1995).…”
Section: Notes On Individual Sourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, radio observations at sub-kiloparsec scales show that the differences between the two families of radio galaxies might arise at distances of a few hundreds of parsecs from the central core (e.g., Lara et al 1999b), a size coincident with that estimated for the narrow line region in Seyfert galaxies (Netzer 1990). Baum et al (1995) conclude, from the study of a sample of FR I and FR II type radio galaxies, that while emissionline gas in FR IIs is photoionized by nuclear UV continuum from the AGN, in FR Is the emission line gas is most possibly energized by the host galaxy itself.…”
Section: The Host Galaxiesmentioning
confidence: 99%
“…Besides this rich radio structure, another peculiarity of 3C 264 is the existence of an optical jet coincident with the radio jet, most possibly of synchrotron nature (Lara et al 1999) and extending up to 2 (0.82 kpc) (Crane et al 1993;Baum et al 1997). There is also evidence of a "ring" around the host galaxy core with a radius between 0.…”
Section: Introductionmentioning
confidence: 96%